Early Childhood Risk and Protective Factors Predicting Resilience against Adolescent Substance Use - Eiden, Rina D. (Advers Resil Sci, 2020)
We examined associations between early childhood (first 3 years of life) risk and protective factors and resilience against adolescent substance use in a prospective sample of alcoholic and non-alcoholic families. We defined resilience as low or no substance use in the context of adversity (having a father with alcohol problems). The sample included 227 families recruited from birth records when children were 12 months old and followed longitudinally to 15–17 years of child ages (n = 182). Adolescents were grouped into 4 categories: Non-challenged (non-alcoholic parent, no adolescent substance use, n = 50), Troubled (non-alcoholic parent, adolescent substance use, n = 30), Resilient (alcoholic parent, no adolescent substance use, n = 36), and Vulnerable (alcoholic parent and adolescent substance use, n = 66). Multivariate analyses were used to examine group differences (resilient vs. vulnerable; non-challenged vs. troubled) in child and parent characteristics and family relationships domains. Children in the troubled group compared to non-challenged had lower effortful control and emotion-regulation, and those in the resilient group were more unadaptable or reactive to novelty compared to the vulnerable group. Parents of resilient compared to vulnerable children reported significantly lower alcohol symptoms and more partner aggression. Finally, fathers of resilient compared to vulnerable children were less aggravated with them in early childhood. Results highlight the importance of continuous measures of alcohol problems, early childhood functioning, and family characteristics for associations with adolescent risk and resilience.Passive gene-environment correlations may account for associations between parent alcohol problem severity and adolescent substance use.